A Jovem Guarda, a Moda, a TV: o papel do programa de televisão na difusão dos padrões da cultura Jovem Guarda nos anos 60 - Santos, Maria Fernanda Malozzi dos (2014)
By the point of changing of cultural standards from 60 s youth generation, this research investigates the creation of a new young Brazilian image built by fashion and spread by Jovem Guarda, a TV program that was created by the advertising agency Magaldi, Maia & Prosperi (MM&P) attending a claim from Record channel and exhibited between 1965 and 1968. Jovem Guarda s presenters were three young singers from that time Roberto Carlos, Erasmo Carlos and Wanderléa that were chosen by MM&P because of their sympathy to support the new image which had been built for youth. Although music is a great Jovem Guarda s characteristic, this research analyses de TV program by the optic of fashion, once music has been studied by others researchers. It was also studied fashion innovations from the 60 s, such as the concept of unisex, the propagation of jeans in Brazilian wardrobe, synthetic fabrics and miniskirts. In this way, this search builds a connection between the TV program and the fashion development. It proves that Jovem Guarda was fundamental in the behavior change and in the young Brazilian 60 s fashion. To achieve these objectives, this research methodology adopts concepts of iconofagia, from Norval Baitello Junior, and image, from Vilém Flusser and Hans Belting. To sustain fashion concept Gilles Lipovetsky s thought about fashion consume is used, as João Braga s historical analyses of national and international fashion. It was also made researches in the Hemeroteca from Mário de Andrade s Library, from São Paulo City hall, and in the Public Archive from São Paulo Estate